(untitled) (Journal of Engineering, 2023)
Institutions and companies are looking to reduce spending on buildings and services according to scientific methods, provided they reach the same purpose but at a lower cost. On this basis, this paper proposes a model to measure and reduce maintenance costs in one of the public sector institutions in Iraq by using performance indicators that fit the nature of the work of this institution and the available data. The paper relied on studying the nature of the institution’s work in the maintenance field and looking at the type of data available to know the type and number of appropriate indicators to create the model. Maintenance data were collected for the previous six years by reviewing the maintenance and financial department records. On this basis, three performance indicators are proposed in creating the model. The result is a model to reduce maintenance costs based on three indicators; each indicator contains a baseline value and a target value. If this model is applied, it will significantly help measure, track, control, and reduce maintenance costs in government institutions.